Investigation of X- and Y-specific single nucleotide polymorphisms in taurine (Bos taurus) and indicine (Bos indicus) cattle - Anderung, C.; Hellborg, L.; Seddon, J.; Hanotte, Olivier H.; Gotherstrom, A. (Wiley, 2007)
Initially, domesticated African cattle were of taurine type. Today, we find both African Bos taurus and Bos indicus cattle, as well as their crossbreeds, on the continent of Africa and they all share the same set of African taurine mitochondrial DNA haplogroups. In this study, we report genetic variation as substitutions and insertions/deletions (indels) on both the X and Y chromosomes, and use the variation to assess hybridization between taurine and indicine cattle. Six African cattle breeds (four Sanga breeds, including Raya Azebu, Danakil, Caprivi, Nguni; and two Zebu breeds, including Kilimanjaro Zebu and South Kavirondo Zebu) were screened for six new X-chromosomal markers, specifically three single nucleotide polymorphisms and three indels in the DDX3X (previously DBX) and ZFX genes, and five previously identified Y-chromosomal markers in the DDX3Y (previously DBY) and ZFY genes. In total, 90 (57 bulls and 33 cows) samples from the African breeds were analysed. We identify five diagnostic haplotypes of indicine and taurine origins on both the X and Y chromosomes. For each breed, the level of indicine introgression varies; in addition to pure taurine, indicine and hybrid X-chromosome individuals, recombinant X-chromosome variants were also detected. These markers are useful molecular tools for assessing the level of indicine admixture in African cattle breeds.